Hukou Changes and Subjective Well-Being - Massimiliano Tani (Institute for the Study of Labor (IZA), 2015)
The literature on subjective well-being has highlighted the negative effects associated with the restrictions and inequality imposed by the hukou system on China's rural population. However, quantifying the cost of holding a rural hukou has generally been problematic, principally for lack of suitable data or measurements. Thanks to RUMiC, a new longitudinal database on China, this limitation can be overcome by exploiting exogenous changes in hukou status due to expropriation. The results support that granting an urban hukou substantially enhances subjective well-being within the household, especially for the household heads. The results complement a growing literature on subjective well-being focusing on China.
Keywords: D19; H13; I31; J61; R20; 330; subjective well-being; expropriation; China